Pertanggungjawaban Hukum Atas Kehilangan Barang Pengguna Jasa di PT. Pos Indonesia (Persero) Kecamatan Sirah Pulau Padang dan Kota Kayuagung - Putri, Tresyah Meyrinda; Emirzon, Joni; Mahfuz, Abdul Latif (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this article is to understand and analyze the legal liability of PT. Pos Indonesia (Persero) Sirah Pulau Padang District and Kayuagung City regarding loss of goods of service users. normative legal research, which focuses on the analysis of applicable legal theories and regulations. The research method used is empirical juridical with primary and secondary data sources. The research results showed that there were several cases of lost goods at PT. Pos Indonesia area. PT. Pos Indonesia, based on its internal regulations and policies, has an obligation to provide compensation to service users in the event of loss of goods. However, the compensation claim process often experiences obstacles and often causes customer dissatisfaction. The recommendation from this research is the need to improve the compensation claim mechanism and increase the quality of service so that public trust in PT. Pos Indonesia can be maintained.